Pengaruh Khalifah Ali Bin Abi Thalib Dalam Lahirnya Ilmu Nahwu: Studi Sejarah Awal Pembentukan Kaidah Bahasa Arab - Farid Ahmad Zulqornaen (PT. Hasba Edukasi Mandiri, 2025)
This article examines the crucial role of Caliph Ali bin Abi Thalib in the development of the science of Nahwu, which became the foundation of Arabic grammar. With a qualitative and descriptive approach, this study analyzes the historical background, driving factors, and the influence of Ali's thoughts on the growth of the science of Nahwu. The findings of the study indicate that Ali bin Abi Thalib, through his assignment to Abu al-Aswad al-Duali, succeeded in laying the foundation for the development of well-structured Arabic language rules. This is very important to maintain the purity of the Qur'an and the understanding of Islamic teachings. Ali's thoughts and contributions are not only relevant in the context of Arabic linguistic history, but also have a lasting impact on Arabic language studies to this day.